Exploratory analysis reveals arthropod consumption in 10 lemur species using DNA metabarcoding. Issue 6 (5th April 2021) - Rowe, Amanda K.; Donohue, Mariah E.; Clare, Elizabeth L.; Drinkwater, Rosie; Koenig, Andreas; Ridgway, Zachary M.; Martin, Luke D.; Nomenjanahary, Eva S.; Zakamanana, François; Randriamanandaza, Lovasoa J.; Rakotonirina, Thierry E.; Wright, Patricia C.
Abstract: Arthropods (insects, spiders, etc.) can fulfill major nutritional requirements for primates, particularly in terms of proteins, fats, vitamins, and minerals. Yet, for many primate species we know very little about the frequency and importance of arthropod consumption. Traditional methods for arthropod prey identification, such as behavioral observations and fecal dissections, offer limited taxonomic resolution and, as a result, underestimate true diversity. Metabarcoding arthropod DNA from primate fecal samples provides a promising but underused alternative. Here, we inventoried arthropod prey diversity in wild lemurs by sequencing two regions of the CO1 gene. Samples were collected opportunistically from 10 species of lemurs inhabiting three national parks in southern Madagascar using a combination of focal animal follows and live trapping. In total, we detected arthropod DNA in 98 of the 170 fecal samples analyzed. Although all lemur species included in these analyses showed evidence of arthropod consumption, those within the family Cheirogaleidae appeared to consume the highest frequency and diversity of arthropods. To our knowledge, this study presents the first evidence of arthropod consumption in Phaner pallescens, Avahi peyrierasi, and Propithecus verreauxi, and identifies 32 families of arthropods as probable food items that have not been published as lemur dietary items to date. Our study emphasizes the importance of arthropods as a nutritional source and the role DNA metabarcoding can play in elucidating an animal's diet. Abstract : Bootstrapped calculations of the probability of arthropod DNA being present in a single fecal sample of each of 10 lemur species from three national parks presented as percentages. Research Highlights: Detected evidence of arthropod consumption in 10 species of lemurs, with Cheirogaleidae species displaying the highest frequency and diversity. First evidence of arthropod consumption in Phaner pallescens, Avahi peyrierasi, and Propithecus verreauxi . Identified 32 families of arthropods as probable lemur food items that have not been previously recognized.